Uncovering differential DNA methylation alterations in subtypes of Acute Myeloid Leukemia - Cardoso, Cândida Patrícia Valente (2021)
Acute myeloid leukemia (AML) is a hematological malignancy where the hematopoietic stem cells or progenitor cells accumulate epigenetic and genetic alterations, losing their differentiation ability and gain proliferative advantage. AML is classified based on the cytogenetic abnormalities detected in the patient’s leukemic cells. The World Health Organization (WHO) classification system is the most used and more current, distinguishing six subgroups. Moreover, the French-American-British (FAB) classification system also classifies AML, distinguishing seven subtypes (M0, M1, M2, M4, M5, M6, M7). The cytogenetic abnormalities and mutations in specific genes also allow the AML stratification into three prognostic risk groups: favorable, intermediate, and adverse. However, not all AML patients’ leukemic cells exhibit chromosomal arrangements or gene mutations with prognostic impact, being categorized in the intermediate prognostic risk group. These patients show high clinical heterogeneity, being the treatment decision a current problem. Our goal was to identify potential prognostic biomarkers of gene expression and DNA methylation that could predict survival in AML patients that were categorized in the intermediate prognostic risk group. Thus, we developed an R-based algorithm that evaluates the prognostic potential of each gene and CpG site, available on the TCGA LAML cohort, in AML patients classified as FAB M1, M2, M4, and M5 subtypes. The algorithm was also performed in a group of patients with AML classified as FAB M0, M1, M2, M4 and M5 together. Our results suggest that there are some genes whose expression and/or DNA methylation are able to subdivide the AML patients categorized in the intermediate prognostic risk group into two subgroups with distinct overall survival. In conclusion, although the patients categorized in the intermediate prognostic risk group show a heterogeneous prognosis, they can be segregated by some candidate prognostic biomarkers of gene expression and DNA methylation, which can help to decide the best therapy for them.